Stock market's assessment of monetary policy transmission: The cash flow effect - Refet S. Gürkaynak; Hatice Gökçe Karasoy-Can; Sang Seok Lee (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
We show that firm liability structure and associated cash flow matter for firm behavior, and that financial market participants price stocks accordingly. Looking at firm level stock price changes around monetary policy announcements, we find that firms that have more cash flow exposure see their stock prices affected more. The stock price reaction depends on the maturity and type of debt issued by the firm, and the forward guidance provided by the Fed. This effect has remained intact during the ZLB period. Importantly, we show that the effect is not a rule of thumb behavior outcome and that the marginal stock market participant actually studies and reacts to the liability structure of firm balance sheets. The cash flow exposure at the time of monetary policy actions predicts future net worth, investment, and assets, verifying the stock pricing decision and also providing evidence of cash flow effects on firms' real behavior. The results hold for S&P500 firms that are usually thought of not being subject to tight financial constraints.
urn:nbn:de:hebis:30:3-515107
Keywords: E43; E44; E52; E58; G14; 330; cash flow effect of monetary policy; investor sophistication; financial frictions; stock pricing